Characteristics of Winter Urban Heat Island in Budapest at Local and Micro Scale - Li, Huawei; Wang, Guifang; Jombach, Sándor (Journal of Environmental Geography, 2020)
Most of the urban heat island (UHI) researches focused on the phenomenon in summer. They mainly studied the causes, different functional areas, and possible mitigation measures to reduce the high temperature in urban areas. However, UHI also exists in winter, but there are a limited number of studies on winter UHI. The characteristics and causes of UHI in winter have not been received much attention or consideration yet. This study aims to characterize the UHI feature in winter in Budapest, Hungary, based on the analysis of land surface temperature (LST) in relation to the factors of elevation, slope exposure, residential type, and snow coverage. Five different Landsat images in the winter season were applied to detect the surface temperature; besides, pictures of the thermal camera at a micro-scale were also used. Results showed that UHI intensity was not strong in winter; built-up areas were warmer than other urban areas. Topography was one of the significant factors affecting the surface temperature in winter. The surface temperature of the hills (300 m asl) was lower than that of the lowlands (below 120 m asl). The south-facing slopes and south oriented buildings were warmer than north-facing slopes and buildings oriented to the north. Areas with snow coverage had a lower temperature than no snow coverage areas. These findings could give general guidance for further UHI research, urban planning as well as landscape design.